2016
DOI: 10.1165/rcmb.2015-0006oc
|View full text |Cite
|
Sign up to set email alerts
|

Protein Kinase Cζ Inhibitor Promotes Resolution of Bleomycin-Induced Acute Lung Injury

Abstract: In premature infants, sepsis is associated with alveolar simplification manifesting as bronchopulmonary dysplasia. The redox-dependent mechanisms underlying sepsis-induced inflammation and alveolar remodeling in the immature lung remain unclear. We developed a neonatal mouse model of sepsisinduced lung injury to investigate whether nicotinamide adenine dinucleotide phosphate oxidase 2 (NOX2) regulates Toll-like receptor (TLR)-mediated inflammation and alveolar remodeling. Six-day-old NOX2 1/1 and NOX2 2/2 mice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 100 publications
0
3
0
Order By: Relevance
“…The pharmacological therapy for pulmonary fibrosis is currently based on corticosteroids and antifibrotic and immunosuppressive agents, which are not always effective. Furthermore, several other therapeutic molecules and pathways with potent antifibrotic effects were described in the past decade, such as metformin, tumor necrosis factor-related apoptosisinducing ligand (TRAIL), pentraxin 3 (PTX3), protein kinase Cz and d, angiotensin/AT2, maresin 1, and aspirin-triggered lipoxin A4 (ATLA/FPR2), which bring new perspectives to the development of an appropriate pharmacological treatment for pulmonary fibrosis (53)(54)(55)(56)(57)(58)(59)(60).…”
Section: Discussionmentioning
confidence: 99%
“…The pharmacological therapy for pulmonary fibrosis is currently based on corticosteroids and antifibrotic and immunosuppressive agents, which are not always effective. Furthermore, several other therapeutic molecules and pathways with potent antifibrotic effects were described in the past decade, such as metformin, tumor necrosis factor-related apoptosisinducing ligand (TRAIL), pentraxin 3 (PTX3), protein kinase Cz and d, angiotensin/AT2, maresin 1, and aspirin-triggered lipoxin A4 (ATLA/FPR2), which bring new perspectives to the development of an appropriate pharmacological treatment for pulmonary fibrosis (53)(54)(55)(56)(57)(58)(59)(60).…”
Section: Discussionmentioning
confidence: 99%
“…In some experiments, lung compliance was monitored during saline infusion using a computer controlled respirator (flexiVent, SCIREQ, Inc., Montreal, Canada) as previous described (24). The pig was paralyzed using rocuronium (1mg/kg) and mechanically ventilated.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies showed that activation of protein kinase C zeta (PKCζ) could promote the apoptosis of VECs and lead to the damage of endothelial integrity and organ functions (Aveleira, Lin, Abcouwer, Ambrósio, & Antonetti, 2010; Buonfiglio et al, 2016; Heo et al, 2011; Kim, Nigro, Fujiwara, Abe, & Berk, 2012; Magnani et al, 2017; Sewduth et al, 2017), and its activity could be regulated by upstream G protein‐coupled receptors and phospholipase C (PLC; van Dijk, Hilkmann, & van Blitterswijk, 1997). PKCζ can be activated by phosphorylation or membrane translocation.…”
Section: Introductionmentioning
confidence: 99%